Activation of astrocytes in the basal forebrain in mice facilitates isoflurane-induced loss of consciousness and prolongs recovery - Jialing Lin; Xuefeng Cheng; Haoyuan Wang; Lin Du; Xiangyu Li; Gaofeng Zhao; Chuangbo Xie (BMC Anesthesiology, 2023)
Abstract Objectives General anesthesia results in a state of unconsciousness that is similar to sleep. In recent years, increasing evidence has reported that astrocytes play a crucial role in regulating sleep. However, whether astrocytes are involved in general anesthesia is unknown. Methods In the present study, the designer receptors exclusively activated by designer drugs (DREADDs) approach was utilized to specifically activate astrocytes in the basal forebrain (BF) and observed its effect on isoflurane anesthesia. One the other side, L-α-aminoadipic acid was used to selectively inhibit astrocytes in the BF and investigated its influence on isoflurane-induced hypnotic effect. During the anesthesia experiment, cortical electroencephalography (EEG) signals were recorded as well. Results The chemogenetic activation group had a significantly shorter isoflurane induction time, longer recovery time, and higher delta power of EEG during anesthesia maintenance and recovery periods than the control group. Inhibition of astrocytes in the BF delayed isoflurane-induced loss of consciousness, promoted recovery, decreased delta power and increased beta and gamma power during maintenance and recovery periods. Conclusions The present study suggests that astrocytes in the BF region are involved in isoflurane anesthesia and may be a potential target for regulating the consciousness state of anesthesia.